Enhancing sustainable business models for green transportation - Simões, V.; Pereira, L.; Dias, Á. (Sustainability, 2023)
Business Models (BMs) are crucial for a successful market penetration and diffusion of sustainable innovations. Nonetheless, the consumer preferences knowledge for adopting electric vehicles (EVs) under Innovative BMs is low. Drawing on existing conceptualizations of BMs, this investigation studies consumers’ preferences for three innovative BMs (EV-Leasing; Battery-Leasing; B2C EV-Sharing) plus the traditional Total Purchase BM. This research aims to analyze the EV’s market growth as well as to understand the consumer’s preferences regarding the business models and understand how it can eliminate the barriers to EV’s purchase. During this study, it was applied an empirical study based on the quantitative method. Data was collected through Google Forms and spread via social media. Using survey data to conduct quantitative analysis, the findings show that most people have an interest in EVs but consider as a main barrier the high costs. Environmental benefits are the main motivation to buy one since these people are very concerned with the envi-ronment. Regarding the Innovative Business Models (IBMs), most people were not aware of their existence but believe that are fundamental for EV’s acquisition.